Locating, Classifying and Countering Agile Land Vehicles With Applications to Command Architectures - Sworder, David D.; Boyd, John E. (Springer International Publishing : Imprint: Springer, 2016)
This book examines real-time target tracking and identification algorithms with a focus on tracking an agile target. The authors look at several problems in which the tradeoff of accuracy and confidence must be made. These issues are explored within the context of specific tracking scenarios chosen to illustrate the tradeoffs in a simple and direct manner. The text covers the Gaussian wavelet estimator (GWE) which has a flexible architecture that is able to fuse uncommon sensor combinations with non-temporal structural constraints.  ·         Discusses applied estimation and prediction of terrestrial targets ·         Covers fusion of heterogeneous sensor types and tracking with non-temporal engagement constraints ·         Examines confidence that the target will be captured and motion analysis of land vehicles.